Exploring the Link Between Emotional Intelligence and Mathematical Problem-Solving Skills Among Grade V Elementary Students in Kepanjen Sub-district - Tety Nur Cholifah; Anisa Rahmawati; Yulia Eka Yanti; Hendra Rustantono; Hamidi Rasyid (AL-ISHLAH: Jurnal Pendidikan, 2024)
Emotional intelligence (EI) plays a crucial role in students' academic performance, particularly in mathematical problem-solving ability (MPSA). This study investigates the level of EI, the level of MPSA, and their relationship in fifth-grade students of Gugus V, Kepanjen District, during the 2021/2022 academic year. This quantitative, correlational study involved 183 fifth-grade students, with a purposive sample of 80 participants. Data collection employed tests to measure MPSA and questionnaires to assess EI. Statistical analysis was conducted using Pearson’s product-moment correlation with SPSS 16.0. The results showed that first, the level of emotional intelligence of grade V elementary school students was mostly in the moderate category, with a percentage of 62.5%. Second, the level of mathematics problem-solving ability of fifth-grade students is mostly in the high category with a percentage of 52.5%. Third, the results of statistical data processing analysis obtained rxy value r table value (0.386 0.286). While the significance value of the analysis results of SPSS 16.0 significance level value of 0.01 (0.000 0.01). These results suggest that higher EI is associated with improved MPSA among fifth-grade students. This underscores the importance of fostering both cognitive and emotional competencies in educational settings. There is a significant positive relationship between EI and MPSA in fifth-grade students. Enhancing EI alongside academic skills may support student success not only in mathematics but across other disciplines and real-life challenges.